Reception Of Umsida Students To “Umsida1912 Instagram” As A Media Of Information On Umsida Students 'Activities: Resepsi Mahasiswa Umsida Terhadap “Instagram Umsida1912” Sebagai Media Informasi Kegiatan Mahasiswa Umsida - Rama Bagus Satria; Ainur Rochmaniah (Academia Open, 2021)
Instagram can be used as a mass communication medium that can reach a wide audience in the digital world, and Instagram users can be categorized as active audiences to play a role in giving meaning to various accounts, especially official accounts at an organization / company / university. No exception the official account from UMSIDA (Muhammadiyah University of Sidoarjo). This account is expected to be a medium of communication between UMSIDA and UMSIDA students. The purpose of this study was to see Umsida Student Reception on "1912 Umsida Instagram" as an Information Media for Umsida Student Activities.This type of research is descriptive qualitative and focuses on the meaning of UMSIDA students (Universitas Muhammadiyah Sidoarjo). The object of this research is Instagram Umsida 1912 and the subjects of this research are students who are followers / followers of the 1912 Umsida Instagram account. The informants are students who are members of UKM (Student Activity Unit) members of HIMA (Student Association) and students who are active in Other organizations outside, the technique of determining informants using purposive sampling, with data obtained from in-depth interviews. The method used in this research is the encoding-decoding reception analysis method by Stuart Hall, where the reception includes perception, thought, preference, and interpretation.The results obtained from this study indicate that the different receptions / meanings by the informants based on the experience and background of each informant are influenced by internal and external factors of the informants that Umsida Instagram is considered to be still lacking in providing information on student activities medically however, Instagram Umsida has advantages in providing information about PMB (New Student Admissions).